Pengaruh Pembebasan Tanah Terhadap Keterlambatan Proyek Pembangunan Jalan Tol Studi Kasus : Jalan Tol Cinere-Jagorawi Seksi II B - Khofiyah, Ovie Lativatul; Angreni, Ida Ayu Ari (Department of Civil Engineering, Diponegoro University, 2019)
Land acquisition for Cinere-Jagorawi toll road section II B should be completed in 2010, but till now (status 15 June 2017) from the need of 17.6 HA, only 16,1353 HA or 91,677% are free. Progress of land acquisition resulted in progress deviation of construction. This study aims to analyze the effect of land acquisition which is resulted in the performance of Cinere-Jagorawi toll road project of section II B late. Data was collected by spreading questionnaires related to the stages and technical implementation of land acquisition, internal factors and external factors inhibiting land acquisition to respondents from Ministry of PUPR, BPN Depok, and community. The result of analysis using regression analysis obtained X15, X17, and X33 as the best variable. The conclusion is, X15 (Funding for public procurement is sourced from the State Budget) with a coefficient of 0.34 as the first influential factor, X17 (Data collection of land status and its document) with the coefficient of 0.257 as the second influential factor, and X33 (Limitations of time for BPN in handling land procurement due to the amount of land to be acquired) with the coefficient of 0.146 as the third influential factor.